2014
DOI: 10.5001/omj.2014.111
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Rhinitis and Associated Comorbidities: Prevalence in Oman with Knowledge Gaps in Literature

Abstract: The prevalence of AR in the adult population presenting with nasal symptoms was found to be 7%, with associated chronic rhinosinusitis present in a third of these patients. However, there appears to be substantial knowledge gaps regarding the association of other comorbidities, like otitis media, bronchitis and bronchial asthma, the long-term outcomes of medical management, and indication of surgical intervention in patients with AR. Future research in AR among Omani patients should aim to address these issues. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
(20 reference statements)
1
10
0
Order By: Relevance
“…However, the result of this study demonstrated that the highest allergy rate was attributed to mites and tree-based allergens (23), which is in line with that of the present study. Al-Abri et al in Oman found that the prevalence of perennial rhinitis was higher than that of the seasonal rhinitis and perennial rhinitis antigen was related to the mites in 80% of the participants (13).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the result of this study demonstrated that the highest allergy rate was attributed to mites and tree-based allergens (23), which is in line with that of the present study. Al-Abri et al in Oman found that the prevalence of perennial rhinitis was higher than that of the seasonal rhinitis and perennial rhinitis antigen was related to the mites in 80% of the participants (13).…”
Section: Discussionmentioning
confidence: 94%
“…Climatic changes and community industrialization are among the main causes of allergic diseases (10,11). Besides, with the epidemiological recognition of the disease and the determination of the prevalence of respiratory allergens, an important step can be taken to promote preventative plans, diagnosis, and treatments for this disease and thus reduce the additional costs which are imposed on the health care system (12,13). Accordingly, this study aimed to investigate respiratory allergens and related factors among patients with allergic rhinitis who referred to a clinic in Shahrekord in the southwest of Iran during 2016.…”
Section: Introductionmentioning
confidence: 99%
“…3 In the Omani population, 80% were found to be sensitive to house dust mites (HDM). 1 This figure was the same as the Malaysian population whereby 72 out of 90 patients were positive to the similar allergen on skin prick test. This constituted exactly 80% of the sample population.…”
mentioning
confidence: 84%
“…2 Despite a different climate pattern, only ten out of 61 patients in Al-Abri's study were categorized as seasonal type, and all of them were sensitive to Russian thistle. 1 Malaysia is a nonseasonal country thus the majority, if not all, patients were of the perennial group. 3 In the Omani population, 80% were found to be sensitive to house dust mites (HDM).…”
mentioning
confidence: 99%
See 1 more Smart Citation